Menstimulasi Kemampuan Berbicara Pada Anak Usia Dini Berbasis Media Dongeng - Agnes Apryliana; Kiki Purwati (LPPM Universitas Muhadi Setiabudi, 2020)
The early childhood education is the first spearhead for children to enjoy education.The need for synergy between teachers and students. The language skills possessed by students require stiulation to improve these abilities. The One of language skill that need to be improved namely the ability to speak. The One method that is considered effective is storytelling. Storytelling is active activity carried out by the teacher to stimulate students speaking abilities.Based on the result of dedication that has been done it can be conclude that the method of storytelling can be used teacher to stimulate students speaking ability at the age of 5-6 years